"We are Humans First": Expanding Learning Outcomes in an Undergraduate Research Methods Course Through an Experiential Learning Project on Homelessness. Issue 3 (3rd July 2018) - Welsh, Megan
Abstract : This paper outlines my approach to and lessons learned from an experiential learning project on homelessness in an undergraduate research methods course for criminal justice majors. Students receive training in research ethics as well as interpretivist research epistemology and methods, and then conduct structured interviews with un-housed individuals. Drawing on a thematic analysis of students' research reflection papers, I discuss three ways in which this approach can enhance and expand learning outcomes beyond what is conventionally achieved in a methods course: (1) developing competency in conducting human subjects research; (2) challenging pre-existing views on social issues; and (3) increasing empathy and enhancing communication skills, which may be particularly important for aspiring law enforcement officers.